Gambaran Kadar Kolesterol Total dan Kejadian Hipertensi di Kelurahan Bandar Buat, Kecamatan Lubuk Kilangan, Kota Padang Tahun 2019 - Muhamad Gerry Fadilla; Eti Yerizel; Desmawati Desmawati (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background, prevalence of hypertension in Indonesia is 34.11%. One of the factors that influence the incidence of hypertension is high levels of the cholesterol in the blood. Objective, to determine the description total cholesterol levels and the incidence of hypertension Methods, thisesearch was a descriptive study with 29 respondents taken using total sampling techniques from secondary data. Results, cholesterol levels were dominated by hyper cholesterolemia (69%), blood pressure was dominated by hypertension (55.2%). the majority are aged> 40 years. hypercholesterolemia sufferers are more frequent in women (76.5%) hypertension sufferers in men (75%). patients with hypercholesterolemia are more often with secondary education (86.7%), patients with hypertension more often with low education (80%). People with hypercholesterolemia tend to have hypertension (37.9%). Conclusion, total cholesterol level dominated by respondents with hyper cholesterolemia, the majority are aged> 40 years, female sex, and have secondary education. The incidence of hypertension is high, with majority sufferers aged> 40 years, male sex and low education.